Comparing the prevalence of Helicobacter pylori and virulence factors cagA, vacA, and dupA in supra-gingival dental plaques of children with and without dental caries: a case-control study - Aida Mehdipour; Parisa Chaboki; Farzaneh Rasouli Asl; Mohammad Aghaali; Negar Sharifinejad; Saeed Shams (BMC, 2022)
Abstract Background Helicobacter pylori infection is one of the most common infectious diseases in humans. Dental plaque is considered as a reservoir of this bacterium, which could play an important role in the development of gastrointestinal problems. Our aim was to investigate the prevalence of H. pylori and its virulence factors in dental plaques in children with and without dental caries. Methods Among children aged 6 to 12 years, a total of 72 children were enrolled in the study, including 36 cases with total DMFT/dmft > 3 (case group) and 36 participants with total DMFT/dmft < 1 (control group). After removing supra-gingival plaques from the lower first permanent molar teeth, the samples were examined using PCR method for the presence of H. pylori and some of its virulence factors. Statistical analysis was performed using chi-square, Fisher' exact test, t-tests, and logistic regression. Results Of 72 participants, 40 cases were male, and 32 cases were female. The minimum and maximum values of total DMFT/dmft indices were zero and ten, respectively, and the mean ± SD value of total DMFT/dmft was 2.78 ± 3.22. Except for vegetable consumption (p = 0.045), there was no significant difference between the two groups regarding gastrointestinal disorders, feeding methods in infancy (p = 0.058), frequency of daily brushing (p = 0.808), frequency of dental visits (p = 0.101), and history of dental scaling (p = 0.246) and professional topical fluoride therapy (p = 0.5). Out of 72 samples, 15 cases were positive for H. pylori DNA (20.8%), and there was no significant association between the presence of this bacterium in dental plaque and dental caries (p = 0.281). The frequency of virulence factors detected in 15 H. pylori cases was as follows: cagA in six cases (40.0%), vacAm1 in three cases (20.0%), and vacAs1 in one case (6.7%). There was no significant difference between the groups regarding the prevalence of virulence factors. Conclusion Our results indicate the presence of H. pylori along with some virulence factors in dental plaques as a reservoir of this bacterium in children in Iran. Although there was no significant association between this bacterium and the incidence of dental caries, dental health in children needs to be seriously taken into consideration.